Exploring the causal relationship between immune cell and all-cause heart failure: a Mendelian randomization study - Li, Jixu; Liu, Liangliang; Luo, Qiuyan; Zhou, Weiyue; Zhu, Yao; Jiang, Weimin (Frontiers in Cardiovascular Medicine, 2024)
Background and objectives Heart failure (HF) is a disease with numerous genetic and environmental factors that affect it. The results of previous studies indicated that immune phenotypes are associated with HF, but there have been inconclusive studies regarding a causal relationship. Therefore, Mendelian randomization (MR) analyses were undertaken to confirm the causal connections between immune phenotypes and HF, providing genetic evidence supporting the association of immune cell factors with HF risk. Methods We selected instrumental variables that met the criteria based on data from the results of genome-wide association studies (GWAS) of immune phenotype and all-cause HF. An evaluation of the causal association between 731 immune cell factors and HF risk was carried out using the inverse variance weighted (IVW), MR-Egger regression (MR-Egger), and weighted median (WM) analysis methods. To determine the horizontal pleiotropy, heterogeneity, and stability of the genetic variants, the MR-Egger intercept test, Cochran's Q test, MR-PRESSO, and leave-one-out sensitivity analysis were performed. Results MR principal method (IVW) analysis showed that a total of 38 immune cell-related factors were significantly causally associated with HF. Further analyses combining three methods (IVW, MR-Egger and WME) showed that six exposure factors significantly associated with heart failure, as shown below. The effect of Dendritic cell Absolute Count, CD62l- CD86+ myeloid Dendritic cell Absolute Count, CD62l- CD86+ myeloid Dendritic cell% Dendritic cell, CD39+ CD8+ T cell% CD8+ T cell, CD3 on Central Memory CD4+ T cell on heart failure was positive. Whereas, a reverse effect was observed for CD14+ CD16+ monocyte% monocyte. Conclusion We investigated the causal relationship between immune phenotypes and all-cause HF. According to the results, Dendritic cell Absolute Count, CD62l- CD86+ myeloid Dendritic cell Absolute Count, CD62l- CD86+ myeloid Dendritic cell% Dendritic cell, CD39+ CD8+ T cell% CD8+ T cell, CD3 on Central Memory CD4+ T cell aggravate HF, and the risk of HF is decreased by CD14+ CD16+ monocyte% monocyte. These phenotypes may serve as new biomarkers, providing new therapeutic insights for the prevention and treatment of all-cause HF.